A Systematic Review of the Clinical Value and Applications of Three-Dimensional Printing in Renal Surgery - Sun, Zhonghua; Lupulescu, C. (MDPI AG, 2019)
The purpose of this systematic review is to collate and analyse the current literature which examines clinical applications of 3D printing for renal disease, alongside cost and time duration factors associated with the printing process. A comprehensive search of the literature was performed across five di erent databases to identify studies that qualitatively and quantitatively assessed the value of 3D-printed kidney models for renal disease. Twenty-seven studies met the selection criteria for inclusion in the review. Twenty-five were original studies, and two were case reports. Of the 22 studies reporting a qualitative evaluation, the analysis of findings demonstrated the value of the 3D-printed models in areas of clinician and patient education, and pre-surgical simulation for complex cases of renal disease. Of five studies performing a quantitative analysis, the analysis of results displayed a high level of spatial and anatomical accuracy amongst models, with benefits including reducing estimated blood loss and risk of intra-operative complications. Fourteen studies evaluated manufacturing costs and time duration, with costs ranging from USD 1 to 1000 per model, and time duration ranging from 15 min to 9 days. This review shows that the use of customised 3D-printed models is valuable in the education of junior surgeons as well as the enhancement of operative skills for senior surgeons due to a superior visualisation of anatomical networks and pathologic morphology compared to volumetric imaging alone. Furthermore, 3D-printed kidney models may facilitate interdisciplinary communication and decision-making regarding the management of patients undergoing operative treatment for renal disease. It cannot be suggested that a more expensive material constitutes a higher level of user-satisfaction and model accuracy. However, higher costs in the manufacturing of the 3D-printed models reported, on average, a slightly shorter time duration for the 3D-printing process and total manufacturing time.